PENGARUH MODEL COOPERATIVE LEARNING TIPE TGT TERHADAP PASSING VOLI SMA WISUDA PONTIANAK - Herdianto Herdianto; Victor G Simanjuntak; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2019)
AbstractThe formulation of the problem was: Is there an influence on the learning model of the Cooperative learning type teams games tournament (TGT) on passing skills under Volleyball ?. This study aimed to determine the effect of cooperative learning model types of teams games tournament (TGT) on volleyball's under-passing ability.The method in this study was an experimental method with pre exprimental design research. The subjects in this study were class XI students with a sample of 31 students.The results showed that there was an effect of the learning model of cooperative learning of students games tournament (TGT) on volleyball's lower passing ability, with the results of the t-test namely, t count> t table (6,303> 1,697), there was a significant effect. Keywords: Teams Games Tournament (TGT), Passing Under Volleyball